Transformasi Relasi Edukatif: Dampak Teknologi Terhadap Interaksi Guru dan Siswa dalam Pembelajaran - Susi, Susi Febriani; Herlianti, Rani; Sangaji, Hardianti Dwi Sasmita; Candra Dewi, Anita (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstrac: This study aims to examine the impact of the use of digital technology on the quality of interaction between teachers and students in the learning process. The scope of the study includes the positive and negative aspects of the integration of digital technology in education, especially in the context of online learning and the use of digital media in the school environment. The method used in this study is a literature review with a qualitative descriptive approach. Data were collected through searching for relevant scientific journal articles published in the last three to four years. The results of the study indicate that digital technology contributes positively to increasing the effectiveness of learning, facilitating broad access to information, enabling personalization of teaching materials, and strengthening collaboration between teachers, students, and parents. However, on the other hand, excessive use of technology can reduce the intensity of face-to-face communication, reduce emotional closeness between teachers and students, and increase the risk of distraction and student dependence on digital devices. In addition, the inequality of digital literacy and teacher competence in utilizing technology is also a significant obstacle. The conclusion of this study emphasizes the importance of a balance between the use of technology and interpersonal interaction in the learning process. An adaptive pedagogical strategy is needed so that technology can be used optimally without sacrificing the humanistic aspects of education.